Developing mediation skills at the tertiary level of education - Gadomska, Agnieszka (Neofilolog, 2024)
The article discusses the need to implement various aspects of mediation, a concept included in CEFR 2003 and updated in the form of new illustrative descriptors in the 2018 CEFR Companion Volume, into English Philology program with reference to students’ needs, the role of mediation in the process of both traditional and online communication. The bottom-up perspective on the selection of mediation descriptors adopted by the author in the project published in the CEFR Companion Volume, Examples from Practice (2022) inspired further changes in the English Studies program. The article presents a model of implementing the mediation-oriented strategies and activities into the syllabi of Practical English, specialization courses, seminars, etc. and discusses their advantages as well as challenges.